Value of Diaphragm Ultrasonography for Extubation: A Single-Blinded Randomized Clinical Trial - Toledo, T. G.; Bacci, M. R. (Critical Care Research and Practice, 2023)
Introduction. Daily evaluation of mechanically ventilated (MV) patients is essential for successful extubation. Proper withdrawal prevents complications and reduces the cost of hospitalization in the intensive care unit (ICU). Diaphragm ultrasonography (DUS) has emerged as a potential instrument for determining whether a patient is ready to be extubated. This study compared the efficacy rate of extubation using a standard withdrawal protocol and DUS in patients with MV. Methods. A randomized, parallel, single-blind, controlled study was conducted on ICU patients undergoing MV. Patients were randomly assigned to either the control (conventional weaning protocol) group or intervention (DUS-guided weaning) group in a 1 : 1 ratio. The primary outcome measure was the rate of reintubation and hospital mortality. Results. Forty patients were randomized to the trial. The mean age of the sample was 70 years, representing an older population. The extubation success rate was 90% in both groups. There was no reintubation in the first 48 hours and only two reintubations in both groups between the second and seventh days. The hospital mortality risk in patients with acute kidney injury was positively correlated with age and the need for hemodialysis. Discussion. This study demonstrates the usefulness of DUS measurement protocols for withdrawing MV. The rate of reintubation was low for both cessation methods. As a parameter, the diaphragm thickness fraction comprehensively evaluates the diaphragm function. The results demonstrate that DUS has the potential to serve as a noninvasive tool for guiding extubation decisions. In conclusion, using DUS in patients with respiratory failure revealed no difference in reintubation rates or mortality compared with the conventional method. Future research should concentrate on larger, multicentered, randomized trials employing a multimodal strategy that combines diaphragmatic parameters with traditional clinical withdrawal indices.